2013
DOI: 10.1080/15524256.2012.758604
|View full text |Cite
|
Sign up to set email alerts
|

Professional and Educational Needs of Hospice and Palliative Care Social Workers

Abstract: In the past decade much growth has occurred in the numbers of patients and families served by hospices and palliative care services. Thus, not surprisingly, these services have also been subject to increasing regulation by governmental and accrediting entities. In order to stay up-to-date in this ever-changing environment and to continue to provide effective interventions, social workers must stay engaged in the professional community and continuing education. In this quantitative study, 1,169 practicing hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…12,61,62 Staff training needs were identified in relation to working with young adults, emotional support provision and developing an advocacy/key working role. Others have found that palliative care professionals have unmet training needs in relation to providing psychosocial support 56,63 and discussing sexual issues. 55 This could be addressed by a combination of formalised training and role modelling, and could involve young people themselves as 'trainers'.…”
Section: Discussionmentioning
confidence: 99%
“…12,61,62 Staff training needs were identified in relation to working with young adults, emotional support provision and developing an advocacy/key working role. Others have found that palliative care professionals have unmet training needs in relation to providing psychosocial support 56,63 and discussing sexual issues. 55 This could be addressed by a combination of formalised training and role modelling, and could involve young people themselves as 'trainers'.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is dearth of empirically based literature on interventions aimed at measuring or improving the emotional state of hospice clients (Reese & Raymer, 2004). In fact, hospice and palliative care social workers themselves have identified the need for continuing education curricula that addresses the psychological and social needs of patients and families and psychosocial interventions that can ameliorate distress (Weisenfluh & Csikai, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As of 2012, qualification for the Hospice and Palliative Medicine subspecialty board required completion of an ACGME-accredited 1-year postgraduate fellowship [13, 14]. As mentioned, palliative care is provided by interdisciplinary speciality teams, and specialist-level training experiences and/or competencies also exist for palliative care nursing [15], social work [16, 17], and chaplaincy [18]. …”
Section: Who Practices Palliative Care?mentioning
confidence: 99%